PARTISIPASI ANGGOTA KELOMPOK TANI DALAM PENGELOLAAN USAHATANI DI DESA MATANI KECAMATAN TUMPAAN - Melgi Yudi Manein; Juliana R. Mandei; Paulus A. Pangemanan (AGRI-SOSIOEKONOMI, 2016)
This study aims to determine how the participation of members of farmers in farm management. The research was carried on in the Matani village of District Tumpaan of South Minahasa regency. Data used in this study are primary data and secondary data. The primary data obtained through direct interviews with respondents, while secondary data obtained from the district office Tumpaan. The sampling technique used was proportional stratified random sampling. The group was divided into two strata , farmer groups and farmer groups. The number of samples taken farmer group is three farmer groups, one advanced farmer group (Karisma) and 2 beginners farmer groups (Beringin and Bina Karya), each farmer groups in the capture of 10 members. The variable that is measured in this study is the participation of members of farmers in the planning, implementation, and controlling by using Likert scale. Analysis of the data used in this research is descriptive analysis. The results showed that, the participation of members of farmers in farm management from planning, implementation, and oversight is high.